PHILOSOPHICAL ANALYSIS OF THE SUFI VIEWS OF ABU ISMAIL ABDULLAH ANSARI (Scientific journal of the Fergana State University, 2025)
This article analyzes the scientific and philosophical foundations of Khoja Abdullah Ansari's teachings on the human soul, the humanism of Sufi ideas, the deep penetration into the spiritual world of man, the passionate thirst to give a divine spark to this spirituality, which is the basis of Sufi philosophy, poetry and ethics. The place of Abdullah Ansari's ideas, the levels of human spiritual elevation in Ansari's teachings, and the views of great Sufi figures on the education of the soul are analyzed philosophically.